2019
DOI: 10.1109/access.2019.2919262
|View full text |Cite
|
Sign up to set email alerts
|

Automated HVAC Control Creation Based on Building Information Modeling (BIM): Ventilation System

Abstract: Building Information Modeling (BIM) is a process that collects building data in a central data model. This data can not only be used to plan and construct a building but to design the controls for heating, ventilation and air conditioning (HVAC) systems. The relevant information about the building and its systems is used as the base for controller design, opening new opportunities like the automated testing and optimization of control strategies, both for energy efficiency and user comfort. This paper shows ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…On the one hand, it examines different functional planning segments in detail. Studies on functional planning segments can be found, for instance, in the areas of architecture [30]- [33] and HVAC (heating, ventilation, air conditioning) [34]- [38]. On the other hand, many research activities focus on topical case studies.…”
Section: Originalitymentioning
confidence: 99%
“…On the one hand, it examines different functional planning segments in detail. Studies on functional planning segments can be found, for instance, in the areas of architecture [30]- [33] and HVAC (heating, ventilation, air conditioning) [34]- [38]. On the other hand, many research activities focus on topical case studies.…”
Section: Originalitymentioning
confidence: 99%
“…The optimized system ensured the daily minimum energy consumption and the thermal comfort of air conditioning [11]. Sporr et al (2019) designed a HVAC control system based on the building information data in BIM. The system could improve the existing control system, thus optimizing the operation energy consumption of building air conditioning equipment [12].…”
Section: Introductionmentioning
confidence: 99%
“…Sporr et al (2019) designed a HVAC control system based on the building information data in BIM. The system could improve the existing control system, thus optimizing the operation energy consumption of building air conditioning equipment [12]. Based on the above studies, it is found that if only the supply of the main power grid and gas network is relied on to meet the needs of users, for the supply side, the energy utilization rate is extremely low, and huge power supply pressure is caused during the peak period of energy consumption, which shortens the service life of the power grid and endangers the security of power supply.…”
Section: Introductionmentioning
confidence: 99%
“…This work derives the BAC creation process using IFC data as a foundation. It is based on the results of a previous paper [5] and extends the control strategy development beyond mere room automation to a more sophisticated and flexible system. Here, a thermal provisioning and distribution system for buildings is taken into account, where control strategies are developed for variable combinations of renewable and fossil energy sources.…”
Section: Introductionmentioning
confidence: 99%